Comparative assessment of intra ocular pressure (IOP) measurements obtained using Goldmann Applanation Tonometer and Non-Contact Tonometer: A cross-sectional study from Maharashtra. - Dr. Kanchan Prakash Wankhede, Dr. Pratik Pradip Walunjkar, Dr. Sourabh Hanumantrao Karad, Dr Varsha Dhakne, Dr. Tushar Kale, Dr. Rahul Washimkar, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Goldmann’s applanation tonometer has received a great importance becausethis method is independent of ocular rigidity it is little influenced by variations in cornealcurvature and it records IOP by directly inflating the cornea in Goldmann’s applanation tonometry surface tension of the tear